Safety of African Swine Fever Vaccine Candidate Lv17/WB/Rie1 in Wild Boar: Overdose and Repeated Doses - Barasona, Jose A.; Cadenas-Fernández, Estefanía; Kosowska, Aleksandra; Barroso-Arévalo, Sandra; Rivera, Belén; Sánchez, Rocío; Porras, Néstor; Gallardo, Carmina; Sánchez-Vizcaíno, Jose M. (Frontiers in Immunology, 2021)
African swine fever (ASF) is a highly lethal infectious disease that affects domestic pigs and wild boar. Outbreaks of ASF have grown considerably in the last decade causing important economic consequences for the swine industry. Its control is hampered by the lack of an effective treatment or vaccine. In Europe, the wild boar is a key wild reservoir for ASF. The results of the oral vaccination trial of wild boar with Lv17/WB/Rie1 are hope for this problem. However, this vaccine candidate has certain safety concerns, since it is a naturally attenuated vaccine. Therefore, the present study aims to evaluate the safety of this vaccine candidate in terms of overdose (high dose) and repeated doses (revaccination) in wild boar. Low-dose orally vaccinated animals developed only a slight transient fever after vaccination and revaccination. This was also the case for most of the high-dose vaccinated wild boar, exception for one of them which succumbed after revaccination. Although this fatality was related to hierarchical fights between animals, we consider that further studies are required for clarification. Considering these new results and the current epidemiological situation of ASF in wild boar, this vaccine prototype is a promising tool for the control of the disease in these wild populations, although further studies are needed.